The Influence of Ancestral Lifeways on Individual Economic Outcomes in Sub-Saharan Africa. Issue 4 (28th September 2018) - Michalopoulos, Stelios; Putterman, Louis; Weil, David N
Abstract: Does a person's historical lineage influence his or her current economic status? Motivated by a large literature in the social sciences stressing the effect of an early transition to agriculture on current economic performance at the country level, we examine the relative contemporary status of individuals as a function of how much their ancestors relied on agriculture during the preindustrial era. We focus on Africa, where—by combining anthropological records of groups with individual-level survey data—we can explore the effect of the historical lifeways of one's forefathers. Within enumeration areas (typically a single village or group of villages in the countryside and a city block in urban areas) as well as occupational groups, we find that individuals from ethnicities that derived a larger share of subsistence from agriculture in the precolonial era are today more educated and wealthy. A tentative exploration of channels suggests that differences in attitudes and beliefs as well as differential treatment by others, including differential political power, may contribute to these divergent outcomes.